The Establishment of Cape Hatteras National Seashore - Brantley, Kristi (East Carolina University, 2016)
This thesis examines the land acquisition process used during the creation of Cape Hatteras National Seashore (CHNS). It analyzes the role of both North Carolina's state government and the federal government in the creation of CHNS. It evaluates research regarding the landowners who refused to sell their land (thus forcing legal action), their arguments speaking to their opposition, and the National Park Service's mission to protect and preserve this land. The methodology used included examination of media and literature published during that time period, exploration of recorded interviews with residents, and investigation of the federal government's plans to create a national seashore. The thirty-one year journey to acquire land for CHNS was unnecessarily painful, frustrating to inhabitants of the Outer Banks, and far more expensive than it should have been. Yet, it served as a learning experience that shaped the National Park Services' performance post-CHNS.
Keywords: National Park Service; Cape Hatteras National Seashore (N.C.)--History; Land use--North Carolina--Outer Banks; Historic preservation--North Carolina--Outer Banks